1990
DOI: 10.1007/978-94-009-1876-4_26
|View full text |Cite
|
Sign up to set email alerts
|

Introduced and cultivated fleshy-fruited plants: consequences of a mutualistic Mediterranean plant-bird system

Abstract: The Montpellier region (Mediterranean France) offers 65 native taxa with fleshy fruits whose seeds are dispersed mainly by bird species. Birds also remove the fleshy fruits of non-native plant species, cultivated ones (e.g. Vitis vinifera ssp. vinifera), weeds (e.g. Phytolacca americana), garden shrubs (e.g. Pyracantha coccinea, Ligustrum ovalifolium). We report that 19 non-native plant species are dispersed by 16 bird species. Grapes constitute a very importand food item for migrating and wintering thrushes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…Stiles (1982) examined Christmas Bird Count data and the increasing popularity of multiflora rose (Rosa multiflora) as a multi-use ornamental in suburban and urban areas. He concluded that there was a causal link between increased planting of R. multiflora and the increased range of Northern Mockingbirds (Mimus polyglottos) in the northeastern U.S. (Stiles 1982).There is also evidence that longer temporal availability of non-native fruits has encouraged migratory birds to postpone migration (Debussche and Isenmann 1990).…”
Section: Consumption By Frugivorous and Omnivorous Birdsmentioning
confidence: 96%
See 1 more Smart Citation
“…Stiles (1982) examined Christmas Bird Count data and the increasing popularity of multiflora rose (Rosa multiflora) as a multi-use ornamental in suburban and urban areas. He concluded that there was a causal link between increased planting of R. multiflora and the increased range of Northern Mockingbirds (Mimus polyglottos) in the northeastern U.S. (Stiles 1982).There is also evidence that longer temporal availability of non-native fruits has encouraged migratory birds to postpone migration (Debussche and Isenmann 1990).…”
Section: Consumption By Frugivorous and Omnivorous Birdsmentioning
confidence: 96%
“…A number of authors have noted birds in the suburban environment responding to the habitats, fruits, and flowers of specific plantings of non-native ornamentals. Obviously, such plants represent a food source to native and non-native birds when other food is scarce or unavailable (Siegfried 1968, Debussche et al 1982, Debussche and Isenmann 1990, White and Stiles 1992.Plants in urban environments occur as patches of ornamental landscapes, urban forests, and greenbelts. Those plants occupying edge areas and gaps produce more fruit than species growing under a closed canopy, even among shade tolerant individuals.…”
mentioning
confidence: 99%
“…The establishment stage involves mainly local dispersal, whereas the spread stage involves rapid expansion that is mostly dominated by LDD (Kot et al 1996 ;Clark 1998 ). In these two post -entry stages, humans play an increasingly important role (see, for example, Von der Lippe & Kowarik 2007 ), yet natural vectors are probably still the key dispersers (Debussche & Isenmann 1990 ;Richardson et al 2000a ;Murphy et al 2008 ;Westcott et al 2008 ). Dispersal at the post -entry stage is crucially important to the extent that successful dispersal away from the initial point of introduction marks the transition from ' alien ' through ' naturalized ' to ' invasive ' ( sensu Richardson et al 2000b ).…”
Section: Advances In D Ata C Ollectionmentioning
confidence: 99%
“…P. coccinea produces fruits profusely and is widely used in gardens and hedges in this region (Debussche and Isenmann 1990;Malric 2004), which makes it a widely available resource for frugivorous birds. In fact, P. coccinea is the most frequent food item in the gizzard contents of the main bird dispersers in the Montpellier region (Debussche andIsenmann 1990, 1994), which suggests that opportunities for seed dispersal are great.…”
Section: Introductionmentioning
confidence: 99%